Pengaruh audit delay dan ukuran KAP terhadap audit switching: Kajian dari sudut pandang klien - Arum Ardianingsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Development  of  business  is  rapidly  increasing  influence  the  development  of  public  accounting profession which affects more Public Accounting Firm (KAP) operating. Number KAP provides many options  for  companies  to  keep  using  the  same  KAP  KAP  or  make  the  turn  (auditor  switching).  This study  aims  to  provide  empirical  evidence  of  the  effect  of  audit  delay  and  the  size  of  KAP  to  audit switching. This study uses two variables independence of consist that audit delay and the size of KAP are supposed to influence the audit switching. Testing performed using logistic regression. Test results obtained  evidence  that  audit  delay  and  the  size  of  KAP  does  not  significantly  influence  the  audit switching. Keywords: Audit Delay, The size of KAP and Audit Switching.